2020
DOI: 10.25646/6900
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and dietary habits of older children and adolescents in Germany – Cross-sectional results of the 2017/18 HBSC study and trends

Abstract: Numerous findings are known to exist between dietary habits, physical activity, and child and adolescent health. Here, we will use data from the most recent Health Behaviour in School-aged Children (HBSC) study to describe dietary habits and patterns of physical activity. Using the survey data for 11-, 13- and 15-year-old students from across Germany, we report findings for key indicators of diet and physical activity for the 2017/18 cycle. By comparing these findings with data from the 2009/10 and 2013/14 sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Our findings also suggest that addressing the socioeconomic and demographic factors contributing to inequalities in health outcomes associated with dietary behaviours may reduce the risk of overweight/obesity while simultaneously increasing the likelihood of good mental health and well-being. This is because, consistent with previous studies [ 14 , 15 , 17 , 29 , 43 , 47 ] we found that dietary behaviours vary across populations based on age, gender and socioeconomic status. Notably, boys tended to consume breakfast and partake in family meals more frequently than girls but consumed fruits and vegetables less frequently.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings also suggest that addressing the socioeconomic and demographic factors contributing to inequalities in health outcomes associated with dietary behaviours may reduce the risk of overweight/obesity while simultaneously increasing the likelihood of good mental health and well-being. This is because, consistent with previous studies [ 14 , 15 , 17 , 29 , 43 , 47 ] we found that dietary behaviours vary across populations based on age, gender and socioeconomic status. Notably, boys tended to consume breakfast and partake in family meals more frequently than girls but consumed fruits and vegetables less frequently.…”
Section: Discussionsupporting
confidence: 93%
“…The developmental stage of the study population may explain some of the observed findings. Prior research suggested that changes in dietary behaviours can occur naturally with age [ 43 , 53 ]. As adolescents grow older, breakfast consumption might decline due to competition with their sleeping time, while increasing autonomy from parents is a typical developmental milestone, and this could contribute to fewer family meals [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It reduces the risk of non-communicable diseases like cardiovascular diseases, type 2 diabetes, and cancer, as well as depressive symptoms and anxiety ( 2 7 ). However, physical inactivity is a major public health problem worldwide and also prevalent in all age groups in Germany ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%